PENGARUH METODE OUTDOOR LEARNING TERHADAP MOTIVASI BELAJAR SISWA KELAS IV PADA MATA PELAJARAN MATEMATIKA DI SDN 185 PALEMBANG - Andini, Elvina; Misdalina, Misdalina; Puspita Sari Jaya, Melinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to find out the effect of the outdoor learning method on the math learning motivation of fourth-grade students at SD Negeri 185 Palembang by using a quantitative approach and a quasi-experimental design. The research sample consisted of class IV C as the control class and class IV D as the experimental class. Data were obtained through a learning motivation questionnaire given before (pretest) and after (posttest) the treatment, then analyzed using an independent sample t-test. The results showed that the average learning motivation of students in the experimental class increased higher compared to the control class, with a significance value of 0.000 < 0.05. During the learning process, students appeared more active, enthusiastic, and easily understood the material through direct learning experiences outside the classroom. Thus, the outdoor learning method has been proven to significantly influence the improvement of students' learning motivation in Mathematics.Keywords: mathematics, learning motivation, outdoor learning, elementary school.